Impact of intensified training and carbohydrate supplementation on immunity and markers of overreaching in highly trained cyclists - Svendsen, I. S.; Killer, S. C.; Carter, J. M.; Randell, R. K.; Jeukendrup, A. E.; Gleeson, M. (European Journal of Applied Physiology, 2016)
Purpose: To determine effects of intensified training (IT) and carbohydrate supplementation on overreaching and immunity. Methods: In a randomized, double-blind, crossover design, 13 male cyclists (age 25 ± 6 years, VO2max 72 ± 5 ml/kg/min) completed two 8-day periods of IT. On one occasion, participants ingested 2 % carbohydrate (L-CHO) beverages before, during and after training sessions. On the second occasion, 6 % carbohydrate (H-CHO) solutions were ingested before, during and after training, with the addition of 20 g of protein in the post-exercise beverage. Blood samples were collected before and immediately after incremental exercise to fatigue on days 1 and 9. Results: In both trials, IT resulted in decreased peak power (375 ± 37 vs. 391 ± 37 W, P < 0.001), maximal heart rate (179 ± 8 vs. 190 ± 10 bpm, P < 0.001) and haematocrit (39 ± 2 vs. 42 ± 2 %, P < 0.001), and increased plasma volume (P < 0.001). Resting plasma cortisol increased while plasma ACTH decreased following IT (P < 0.05), with no between-trial differences. Following IT, antigen-stimulated whole blood culture production of IL-1a was higher in L-CHO than H-CHO (0.70 (95 % CI 0.52-0.95) pg/ml versus 0.33 (0.24-0.45) pg/ml, P < 0.01), as was production of IL-1ß (9.3 (95 % CI 7-10.4) pg/ml versus 6.0 (5.0-7.8) pg/ml, P < 0.05). Circulating total leukocytes (P < 0.05) and neutrophils (P < 0.01) at rest increased following IT, as did neutrophil:lymphocyte ratio and percentage CD4+ lymphocytes (P < 0.05), with no between-trial differences. Conclusion: IT resulted in symptoms consistent with overreaching, although immunological changes were modest. Higher carbohydrate intake was not able to alleviate physiological/immunological disturbances.